What are the most frequent movement combinations leading to goals in professional male and female soccer? - Hernandez, D. M.; Jones, P. (European Journal of Human Movement, 2026)
Different studies have analysed the movements performed in key moments of a soccer match such as goal scoring situation. Anyhow, no study has analysed how these movements are combined. This study aimed to identify the most habitual combination of movements occurring before a goal in the English Premier League and Women`s Super League. Data was collected through video-analysis using a modified version of the Bloomfield Movement Classification. The frequency of each of the movements performed before and after a selected movement (for example, linear advancing motion) was analysed in both English Premier League and Women`s Super League. Linear advancing motion, deceleration and turn in different orders accounted for 25.3% and 22.9% of individual involvements in Premier League and Women`s Super League, respectively. The most common movement before a linear advancing motion was a turn, while the most common movement performed after was a deceleration. Decelerations were most frequently preceded by a linear advancing motion and followed by a turn. Turns were most preceded and followed by deceleration and turn, respectively. Male and female professional soccer players are exposed to different sequences of actions before a goal. Within this, the combination of linear advancing motion, turn and deceleration is the most commonly performed, usually following a particular order. Coaches and trainers should focus on improving players' proficiency in transitioning between these various movements, with special attention to the most common sequences observed.